PERKEMBANGAN INDANG SUNGAI TAREH NAGARI BALAH AIE UTARA KECAMATAN VII KOTO KABUPATEN PADANG PARIAMAN - Mastajabul Hakum; Darmawati Darmawati; Afifah Asriati (SENDRATASIK UNP, 2018)
AbstractThis article aims to describe on the development of Dance in Indang Tareh River Nagari Balah Aie North Sub-district VII Koto Padang Pariaman. This study aims to describe the development of Indang Dance in Sungai Tareh Nagari Balah Aie Utara VII Koto Sub District Padang Pariaman District. This research was a qualitative research with descriptive analysis method. The object of this research was the development of Indang Jorong Sungai Tareh Nagari Balah Aie Utara VII Koto Sub District Padang Pariaman District. The instruments of this research were the researcher selves and researcher was assisted by supporting instruments such as notebooks, pens, voice recorders and camera. Techniques of data collection were done by way of literature study, observation, interview and documentation. Techniques of data analysis were done by step of grouping, analyzing, and describing the data. The results showed that Indang dance of Sungai Tareh is a traditional art in Nagari Balah Aie Utara District VII Koto Padang Pariaman District. Indang dance of Sungai Tareh is used as entertainment at traditional ceremonies, entertainment at weddings and other entertainment. The Sungai Tareh Indang dance is served in the form of tigo sandiang at alek nagari and solo performance at the wedding party. In Indang dance of Sungai Tareh uses internal and external music. Numbers of dancers are 13 dancers and 1 person is tukang dikie. Costumes used are guntiang cino costume, kain sarung, and deta. Quantitatively, Sungai Tareh Indang dance has undergone the development and has been performed in the neighbouring area such as Pekanbaru, sawah lunto, bawan pasaman, and experiencing the development of usability from as a broadcaster of Islam and Alek nagari to the wedding party.Key words: Development, Indang River Tareh